2004
DOI: 10.1021/jp047035w
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal ZnSe, ZnSe/ZnS, and ZnSe/ZnSeS Quantum Dots Synthesized from ZnO

Abstract: Colloidal ZnSe quantum dots were successfully synthesized from ZnO in a lauric acid/hexadecylamine mixture. X-ray diffraction patterns indicated that the ZnSe quantum dots possess a wurtzite structure. Transmission electron microscope images of the quantum dots showed that the average diameter are in the range of 25∼60 Å. The size-dependent photoluminescence was controlled from 400 to 440 nm with the quantum yields of 6∼10% at room temperature. After passivation with 1.8 monolayer of ZnS overcoat by a traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 28 publications
(54 reference statements)
3
94
2
1
Order By: Relevance
“…ZnSe quantum dots were prepared as described. [14] The DLS data show a diameter of (1.3 AE 0.5) nm for Pt 5 nanoclusters, which is much smaller than that of ZeSe quantum dots (7 nm).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…ZnSe quantum dots were prepared as described. [14] The DLS data show a diameter of (1.3 AE 0.5) nm for Pt 5 nanoclusters, which is much smaller than that of ZeSe quantum dots (7 nm).…”
Section: Methodsmentioning
confidence: 92%
“…The QY for the Pt 5 nanoclusters was found to be 18 % in water, while that for another blue photoluminescent species, ZnSe quantum dots in chloroform, was 5 %. [14] On the other hand, we measured the absolute QY of newly synthesized Au 8 nanoclusters [15] and found that the QY is 3.3 % [2] in water. Absolute QY measurements show that the fluorescence of Pt 5 nanoclusters is at least three times brighter than that of ZnSe quantum dots and Au 8 nanoclusters.…”
mentioning
confidence: 99%
“…4) [261]. The relations between the positions of the exciton and "defect" emission maxima and the particle size were obtained for nanoparticles of CdS [21, 42, 46, 77-79, 82, 83, 90, 92, 98, 99, 114, 116, 118, 119, 123, 126, 130, 131, 133, 138, 139, 305-307], HgS [83,144], MoS 2 [160], ZnS [83,[152][153][154][155][156]308], PbS [163,167,168], In 2 S 3 [158], Cu x S [174], CdSe [24, 46, 48, 71, 205, 212-223, 226, 228, 229, 253, 309], CdSe/ZnS [234,235], CdSe/CdS [223,236], ZnSe [244,245,247], PbSe [73,241,242], HgSe [310], CdTe [51, 253-259, 265, 269, 271, 272, 304, 310, 311], CdSe x Te 1-x [239,240,294], CuInSe 2x Te 2(1-x) [252], AgI [276], AgBr [273], CuBr [279], CuCl [4], PbI 2 [282], ZnO [77, 178-180, 184, 188, 295, 312-315], TiO 2 [190,194], In 2 O 3 [316], CeO 2 [134], Al 2 O 3 …”
Section: Luminescence* Of Semiconductor Nanocrystalsmentioning
confidence: 99%
“…The particles are dispersed and suspended homogeneously in the colloidal solution [11]. Some of the techniques associated with the synthesis of colloidal CdSe and ZnSe quantum dots are chemical synthesis [12,13], photochemical Appl. Sci.…”
Section: Introductionmentioning
confidence: 99%